2005
DOI: 10.1080/09723757.2005.11885914
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Null Genotype at Glutathione S-transferase M1 Locus as a Risk Factor for Oral Squamous Cell Carcinoma in Indian Tobacco Users

Abstract: Inter-individual differences in sensitivity to chemical carcinogens may contribute to differences in susceptibility to human cancer subsequent to environmental exposures. It has been reported that polymorphisms in glutathione S-transferase (GST) and cytochrome P-450 oxidase (CYP) genes are associated with increased risk of tobacco-related cancers in different ethnic populations. In this study, we investigated polymorphisms in GSTM1, GSTT1, CYP1A1 and CYP2E1 genes in 80 oral squamous cell carcinoma (SCC) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…Another study reported strong associations of the same polymorphisms among OCs, leukoplakia and submucous fibrosis patients, but the degrees of associations were lower than the earlier studies [18]. The same study was carried out on the Bengali population of Eastern India taking OCs and Leukoplakias into account also showed significant associations in this regard [19,34]. Our study apart from the NMPs also showed similar associations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another study reported strong associations of the same polymorphisms among OCs, leukoplakia and submucous fibrosis patients, but the degrees of associations were lower than the earlier studies [18]. The same study was carried out on the Bengali population of Eastern India taking OCs and Leukoplakias into account also showed significant associations in this regard [19,34]. Our study apart from the NMPs also showed similar associations.…”
Section: Discussionsupporting
confidence: 84%
“…There are also evidences of negative correlations in combination analyses [34,35]. However, no relation between polymorphisms of combined GSTM1 and GSTT1 null genotypes was found with nonmalignant oral lesions in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…Number of female smokers was very less, so it was not possible to compare the results between both the genders. No significant differences were observed between smokers and non-smokers, alcoholic and non-alcoholic individuals, tobacco chewers and non-chewers, carrying homozygous GSTM1/GSTT1/GSTM1T1 null genotype (p>0.05) ( Anantharaman, 2007;Buch et al, 2002;Nair et al, 1999 South Indians c 1744 485 (27.8)** 242 (13.9) 136 (7.8) Naveen et al, 2004;Samson, 2007;Shehnaz et al, 2011;Sreelekha et al, 2001;Suneetha, 2011;Vettriselvi et al, 2006;Vijayalakshmi et al, 2005 East Indians d 67 18(27.0) 9 (13.0) Sikdar et al, 2005 Central Indians e 282 99 (35.1) 37 (13.0) Devi et al, 2008 North Nair et al, 1999;Singh et al, 2009 Blacks b 3008 960 (31.9) 744 (24.9)* 298 (9.9)* Adams et al, 2003;Benzamin et al, 2011;Coutinho et al, 2010;Dandara et al, 2002;Lavender et al, 2009;Masimirembwa et al, 1998;Millikan et al, 2000;Rossini et al, 2002 Caucasians c 2674 1064/2232 (47.7)* 448/2674 (16.7) 31 (9.3) Amer et al, 2011;Baranova et al, 1997;Chen et al, 1996;D'Alo et al, 2004;Gsur et al, 2001;Kargas et al, 2003;Millikan et al, 2000;Mitrunen et al, 2001;Steinhoff et al, 2000;Welfare et al, 1999 Asians 1). The frequency distribution of GSTM1 and GSTT1 alleles were compared between different states of India and other populations all over the world (Table 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…A significant association between CYP1A1 Val allele and increased risk for oral cancer risk was observed in an American‐based study, whereas another study did not find an association between CYP1A1 Ile/Val and head and neck cancer risk 29, 30. A study conducted inKeralite population (98 cases and 60 controls) of south India31 reported high risk of oral canceramong tobacco users carrying CYP1A1*2C polymorphism, whereas there was no association for CYP1A1*2A polymorphism and oral squamous cell carcinoma in another study done in Kolkata population of eastern India (80 cases and 67 controls) 32. Both the reports are contrary to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have been done in Germans27, 28 and American whites 29, 30. Another study conducted in Keralite population of south India demonstrated a positive association between CYP1A1*2C polymorphism and oral cancer,31 whereas a study done in eastern part of India indicated a negative correlation between CYP1A1*2A polymorphism and oral squamous cell carcinoma 32. Hence, there are conflicting results regarding the association between CYP1A1*2A and CYP1A1*2C genotypes and the risk of UADT cancers in various ethnic groups.…”
mentioning
confidence: 99%